Why Not an Opioid Epidemic in Europe Like in the USA? - Soriano, Vicente (AIDS Reviews, 2020)
The CDC reported 70,237 drug overdose deaths in the United States in 2017 (Scholl et al., MMWR 2018; 67: 1419-27). Sadly, this yearly rate has been increasing significantly during the past two decades. Opioids, mostly synthetic drugs other than methadone, and particularly fentanyl, are currently the major responsible of drug overdose deaths (Fig. 1). The US states with the highest fatality rates due to drug overdose are West Virginia, Ohio, Pennsylvania, the District of Columbia, and Kentucky.
Keywords: Scopus; JCR